Impact of Social Vulnerability on Cardiac Arrest Mortality in the United States, 2016 to 2020 - Karthik Gonuguntla; Muchi Ditah Chobufo; Ayesha Shaik; Neel Patel; Mouna Penmetsa; Yasar Sattar; Harshith Thyagaturu; Carlson Sama; Anas Alharbi; Paul S. Chan; Sudarshan Balla (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Cardiac arrest is 1 of the leading causes of morbidity and mortality, with an estimated 340 000 out‐of‐hospital and 292 000 in‐hospital cardiac arrest events per year in the United States. Survival rates are lower in certain racial and socioeconomic groups. Methods and Results We performed a county‐level cross‐sectional longitudinal study using the Centers for Disease Control and Prevention's Wide‐Ranging Online Data for Epidemiologic Research multiple causes of death data set between 2016 and 2020 among individuals of all ages whose death was attributed to cardiac arrest. The Social Vulnerability Index is a composite measure that includes socioeconomic vulnerability, household composition, disability, individuals from racial and ethnic minority groups status and language, and housing and transportation domains. We examined the impact of social determinants on cardiac arrest mortality stratified by age, race, ethnicity, and sex in the United States. All age‐adjusted mortality rate (cardiac arrest AAMRs) are reported as per 100 000. Overall cardiac arrest AAMR during the study period was 95.6. The cardiac arrest AAMR was higher for men compared with women (119.6 versus 89.9) and for the Black population compared with the White population (150.4 versus 92.3). The cardiac arrest AAMR increased from 64.8 in counties in quintile 1 of Social Vulnerability Index to 141 in quintile 5, with an average increase of 13% (95% CI, 9.8%–16.9%) in AAMR per quintile increase. Conclusions Mortality from cardiac arrest varies widely, with a >2‐fold difference between the counties with the highest and lowest social vulnerability, highlighting the differential burden of cardiac arrest deaths throughout the United States based on social determinants of health.